STRATEGI MAHASISWA FISIP UNRI DALAM MENGEMBANGKAN USAHA - Ifni, Ditha Yulia; Marnelly, T. Romi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The strategy of FISIP UNRI students in developing their business. This research was carried out on the campus of FISIP UNRI. The purpose of this research is to find out how the obstacles faced in running a business for these students and to know the form of strategic options used by fisip students who are entrepreneurial with the aim of developing the business. During the research, the determination of the subject was done using purposive sampling techniques that have been determined criteria based on the needs of this research. From the existing criteria, 4 informants were taken as the subject of this study which was adjusted to the products produced by each informant. Then in carrying out this research the theory used was the rational choice of the character James S. Colleman. In this theory there are 2 aspects, namely actors (students) and aspects of resources (products). From both aspects, each of them looks at the form of choice of strategies used by informants that for them can provide an advantage during the running of a business or business and this is certainly based on the business obstacles they have experienced. The result of this study is in entrepreneurship there is such a thing as entrepreneurial barriers. These entrepreneurial barriers can be caused by different consumer perspectives, insufficient capital, business competition and other factors. Based on the obstacles they experience, the informant as a student who has a business trying to see the choice of strategy in terms of how to determine the product, price, location, promotion process to the sales process.Â Key words: Entrepreneurship, Strategy, Constraints.Â